Effects of frequency of supplementation on the intake and digestion of low-quality forage by beef steers - Farmer, C.G.; Cochran, R.C.; Simms, D.D.; Klevesahl, E.A.; Wickersham, T.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 43% CP (dry basis) supplement was fed to 16 ruminally fistulated steers on 2, 3, 5, or 7 days a week. Supplement was offered at .36% BW (dry basis) daily for steers that received supplement every day. For other treatments, the same amount of supplement was split equally among supplementation events. Forage intake and digestibility increased with increasing supplementation frequency. However, the difference in forage intake tended (cubic, P=.07) to be most prominent for the two extremes; the 3- and 5-days-a-week treatments tended to be similar. Forage intake for steers supplemented on 2 days a week decreased on the days when they were supplemented. Although forage utilization may improve with increasing frequency of supplementation, the impact on performance is likely to be small unless differences in frequency of supplementation are extreme.
Keywords: Beef; Steers; Forage; Intake; Digestion; Supplementation frequency